Regional bioeconomies: public finance and sustainable policy narratives. Issue 2 (3rd April 2021) - Albrecht, Moritz; Grundel, Ida; Morales, Diana
ABSTRACT: Regional bioeconomies promote sustainable, regional economies under the auspices of EU green growth policies. Combining prospects of rural rejuvenation, sustainability and innovation, they are employed to address climate change, societal challenges, and often benefit from substantial public funds. Yet, despite public finance's key role for bio-based transitions and (regional) bioeconomies, it has received little academic attention. Framed by conceptualisations on greening finance and (sustainable) policy narratives, this paper evaluates the public finance processes of three spatially variegated regional bioeconomy developments in Europe (Finland, Sweden, Spain). It provides empirical accounts from the case study sites and contrasts their public finance narratives with sustainable bioeconomy policy trajectories employed in EU policy promotion and benchmarking. This critical questioning of the current representations of regional bioeconomies in public finance narratives portrays a problematic mismatch between the dominant selective economic features and wider EU policy aims, particularly in relation to sustainability. Accompanied by the neglect of decisive local features in these benchmarking narratives, they promote a sustainably and spatially unreflective path forward for bioeconomy policy learning and development.